Genetic polymorphism of catechol-O-methyltransferase modulates the association of green tea consumption and lung cancer. Issue 4 (July 2019) - Lai, Chung-Yu; Kerr, Chih-Ling; Huang, Chia-Chen; Chen, Chun-Chieh; Tsai, Chin-Hung; Tang, Yu-Min; Chen, Pei-Yu; Chen, You-Rong; Wong, Ruey-Hong
Abstract : Tea polyphenols are strong antioxidants, which can be rapidly O- methylated by catechol- O -methyltransferase (COMT). Thus, it is possible that the genetic polymorphism of COMT can modulate the association of green tea consumption and lung cancer. Here, we designed a case–control study to evaluate the combined effect of green tea consumption and COMT genotypes on the risk of lung cancer. A total of 237 lung cancer patients and 474 healthy controls were recruited. Questionnaires were administered to obtain demographic data, smoking status, green tea consumption, fruits and vegetables intake, exposure to cooking fumes, and family history of lung cancer. Genotypes for COMT were identified by PCR. Smoking, green tea consumption, exposure to cooking fumes, and family history of lung cancer were associated with the development of lung cancer. When green tea drinkers carrying COMT HL/LL genotypes were selected as the reference group, drinkers carrying the COMT HH genotype had a higher risk for the development of lung cancer (odds ratio: 1.97, 95% confidence interval: 0.99–3.91). Among the current and ever smokers, the elevated risk for lung cancer was more apparent in green tea drinkers carrying the COMT HH genotype compared with green tea drinkers carrying COMT HL/LL genotypes (odds ratio: 5.84, 95% confidence interval: 1.75–19.45). Green tea drinkers with greater activity of the COMT genotype, whereby polyphenols are effectively excluded, will gain fewer protective benefits against lung cancer development.